Analisis Yuridis Penistaan Agama di Media Sosial Menurut Hak Asasi Manusia - Aime Sumolangi; Emma V. T. Senewe; Caecilia J. J. Waha (Departement of Mathematics Education, 2023)
Freedom of expression through social media is one of the rights guaranteed in international human rights agreements. Nonetheless, this freedom can create conflict if freedom of expression is used to insult or harass certain groups or religions. This thesis will examine the juridical analysis of religious blasphemy on social media according to human rights. The criminalization of blasphemy in Indonesia is primarily based on two legal documents. Article 156(a) of the Criminal Code criminalizes the expression